Overview of the lipid profile of hypertension patients at the installation of the Siti Rahmah RSI Padang outpatient clinic in 2021 - Prima Adelin Prima Adelin; Yolanda Rahma Donni; Fionaliza; Rahma Triyana; Melya Susanti (Science Midwifery, 2023)
Hypertension is a health problem that occurs in both developed and developing countries. The risk factors for hypertension are divided into 2, namely modifiable and non-modifiable factors. Modifiable factors are obesity, stress, smoking, drinking alcohol, excessive salt consumption, and dyslipidemia. Factors that cannot be modified are genetics, age, and gender. Dyslipidemia is a condition of abnormal levels of lipid profiles in the blood, namely an increase in total cholesterol, triglycerides, LDL cholesterol (Low Density Lipoprotein) and or a decrease in HDL cholesterol (High Density Lipoprotein). This study aims to see a description of the lipid profile of hypertension patients at the outpatient installation of Siti Rahmah Hospital, Padang in 2021. This study uses a descriptive method with a cross-sectional data collection approach. Based on the research conducted, it was found that most hypertension patients had no complications, as many as 195 people (81.93%), Most hypertension patients had normal LDL (Low Density Lipoprotein) and HDL (High Density Lipoprotein) cholesterol levels as much as 81.09%. and 47.06%, most of the hypertensive patients had high triglyceride and total cholesterol levels as much as 79.83% and 69.33% respectively. Based on the results of the study, it can be concluded that the lipid profile that affects the occurrence of hypertension is triglyceride levels and total cholesterol levels.